Characteristics of drug safety alerts issued by the Spanish Medicines Agency - Montané, Eva; Santesmases, Javier (Frontiers in Pharmacology, 2023)
Objectives: To describe the characteristics of the safety alerts issued by the Spanish Medicines Agency (AEMPS) and the Spanish Pharmacovigilance System over a 7-year period as well as regulatory actions they generated. Methods: A retrospective analysis was carried out of drug safety alerts published on AEMPS website from 1 January 2013 to 31 December 2019. Alerts that were not drug-related or were addressed to patients rathen than healthcare professionals were excluded. Results: During the study period, 126 safety alerts were issued, 12 of which were excluded because they were not related to drugs or were addressed to patients, and 22 others were excluded as they were duplications of previous alerts. The remaining 92 alerts reported 147 adverse drug reactions (ADRs) involving 84 drugs. The most frequent source of information triggering aa safety alert was spontaneous reporting (32.6%). Four alerts (4.3%) specifically addressed health issued related to children. ADRs were considered serious in 85.9% of alerts. The most frequent ADRs were hepatitis (seven alerts) and congenital malformations (five alerts), and the most frequent drug classes involved were antineoplastic and immunomodulating agents (23%). Regarding drugs involved, 22 (26.2%) were ‘under additional monitoring’. Regulatory actions induced changes in the Summary of Product Characteristics in 44.6% of alerts and in eight cases (8.7%) the alert led to the withdrawal from the market withdrawn of medicines with an unfavourable benefit/risk ratio. Conclusions: This study provides an overview of drug safety alerts issued by the Spanish Medicines Agency over a 7-year period and highlights the contribution of spontaneous reporting of ADRs and the need to assess safety throughout the life cycle of medicines.